Akidah Ekonomi Islam - Kurniawan, Adi (Ijtihad, 2015)
Humans ini their daily activities can not be seperated from a conviction, and convidence exist in every human being. Belief that someone will affect the thingking and attitudes, including how he runs an economic activity in searching and getting rizki. Various economic system in the world can not be separated from a faith, so that shows a typical syakhsiyyah. Western economics formulate various activities by relying on the theory and analysis that they believe to be the truth, the Malthus theory as basis for taking action, whereas in Islam, has described how a Muslim run economic activity rests on two main sources if Islamic law, the al-Quran and sunnah, and that is the source of Islamic economics.